2018
DOI: 10.1590/1414-431x20187256
|View full text |Cite
|
Sign up to set email alerts
|

Improved antimelanogenesis and antioxidant effects of polysaccharide from Cuscuta chinensis Lam seeds after enzymatic hydrolysis

Abstract: Cuscuta chinensis polysaccharide (CPS) was extracted using hot water and enzymatically hydrolyzed C. chinensis polysaccharide (ECPS) was produced by the mannase enzymatic hydrolysis process. The purpose of this research was to investigate the antimelanogenic activity of ECPS and CPS in B16F10 melanoma cells. The in vitro antioxidant activity was assessed by their ferric iron reducing power and DPPH free radical scavenging activities. The molecular mass distribution of polysaccharides was determined using SEC-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Tyrosinase and tyrosinase-related protein-1 (TRP-1) play a major role in melanogenesis pathways [23]. Activation of tyrosinase and TRP-1 enhances melanocyte inducing transcription factor (MITF) protein expression, which in turn causes the increase of melanin synthesis [24]. It could be deduced from this study that S. columbaria has the potential to attenuate overproduction of melanin and hyperpigmentation in skin cells.…”
Section: Discussionmentioning
confidence: 83%
“…Tyrosinase and tyrosinase-related protein-1 (TRP-1) play a major role in melanogenesis pathways [23]. Activation of tyrosinase and TRP-1 enhances melanocyte inducing transcription factor (MITF) protein expression, which in turn causes the increase of melanin synthesis [24]. It could be deduced from this study that S. columbaria has the potential to attenuate overproduction of melanin and hyperpigmentation in skin cells.…”
Section: Discussionmentioning
confidence: 83%
“…The mother liquor was fractionated over CC (SiO 2 , hexane/AcOEt 100 : 0 to 0 : 100, then AcOEt/ MeOH 100:0 to 75 : 25) to afford 13 fractions (Frs. [1][2][3][4][5][6][7][8][9][10][11][12][13]…”
Section: Extraction and Isolationmentioning
confidence: 99%
“…Low molecular weight polysaccharide could overcome these problems. Previous researches have reported that enzymatically degraded polysaccharide possesses higher antioxidative, antimelanogenesis, and moisture-preserving activities than the crude polysaccharide 10 , 12 . Besides, increasing evidence has shown that low molecular weight polysaccharide exerts anticancer effects toward different tumors, such as ovarian cancer, colon cancer, and prostate cancer 13 .…”
Section: Introductionmentioning
confidence: 96%
“…Polysaccharides are the main active components of G. lucidum and exert a wide range of pharmacological activities, including immunomodulation, anticolon carcinoma, and antioxidation effects 8 , 9 . The pharmacological activities of polysaccharides are closely related to their molecular structures, including sulfate content, viscosity, average molecular weight, and monosaccharide proportion 10 . High molecular weights, structural complexity, and viscous properties of crude polysaccharides may hinder their clinical application, particularly as therapeutic agents 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation